Leaf growth of hybrid poplar following exposure to elevated CO2 - Gardner, Simon D L (The New phytologist, 1995)
Leaf extension was stimulated following exposure of three interamerican hybrid poplar clones (Populus trichocarpa P. deltoides); 'Unal', 'Boelare', and 'Beaupre' and a euramerican clone 'Primo' (Populus nigra×P. deltoides) to elevated CO2 , in controlled environment chambers. For all three interamerican clones the evidence suggests that this was the result of increased leaf cell expansion associated with enhanced cell wall extensibility (WEx), measured as tensiomerric increases in cell wall plasticity. For the interameriean clone 'Boelare', there was also a significant increase in cell wall elasticity following exposure to elevated CO2 (P⩽ 0.001). The effect of elevated CO2 in stimulating cell wall extensibility was confirmed in a detailed spatial analysis of extensibility made across the lamina of expanding leaves of the clone 'Boelare'. For two of the interamerican hybrids, 'Unal' and 'Beaupre', both leaf cell water potential Ψ and turgor pressure (P) were lower in elevated than in ambient CO2 . By contrast, no significant effects on the cell wall properties or leaf water relations for the euramerican hybrid 'Primo' were observed following exposure to elevated CO2 . suggesting that the mechanism for increased leaf extension in elevated CO2 , differed, depending on clone. The cumulative total length of leaves of 'Boelare' grown in elevated CO2 , was significantly increased (P≤ 0.05) and since leaf number was not significantly increased in any inter-american clone it is hypothesized that final leaf size was stimulated in elevated CO2 for these clones. By contrast, there was no significant effect of CO2 on cumulative total leaf length for the euramerican clone 'Primo', but leaf number was significantly increased by elevated CO2 . The measurements suggest that total tree leaf area was stimulated for a range of poplar hybrids exposed to elevated CO2 . Given the short rotation of a coppiced crop, it is likely that increased leaf areas will result in enhanced stemwood production when hybrid poplars are grown in the CO, concentrations predicted for the next century